The role of neighbourhood density in transposed-letter priming. - Kinoshita S; Castles A; Davis C (Language & Cognitive Processes, 2009)
We investigated how transposed-letter (TL) priming effects are modulated by neighbourhood density in lexical decision task and cross-case same-different task. Robust identity priming and TL priming effects were observed in both tasks. Neighbourhood density facilitated 'word' decisions and reduced the size of identity priming effect in the lexical decision task. It had no effect on the same-different task, and did not modulate identity or TL priming. We take these results as indicating that neighbourhood density modulates priming during lexical access. In the lexical decision task, the difference between identity priming and TL priming was reduced for words from high-density neighbourhood. The last finding is at odds with the 'lexical tuning' hypothesis which has been used to explain modulatory effects of neighbourhood density on masked form priming effects.We also discuss implication of the results for various letter position coding schemes.